2007
DOI: 10.1111/j.1365-4632.2007.03192.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin color measurement in Chinese female population: analysis of 407 cases from 4 major cities of China

Abstract: The authors believed that the present results might basically represent the complexion conditions of Chinese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 13 publications
6
27
0
Order By: Relevance
“…On the other hand, a* already appeared to have returned to its previous value 1 month after treatment, which implies that darkening of the skin lasted longer than reddening after radiotherapy. These objective methods enabled us to compare the results of several reported studies in terms of racial variations [17,25]. For example, the b* value was changed by the addition of radiotherapy to yellowish in a statistically significant manner in Momm's study [4], but was not significant according to our data, partly because of pre-existing ethnic color variations ( Table 2).…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, a* already appeared to have returned to its previous value 1 month after treatment, which implies that darkening of the skin lasted longer than reddening after radiotherapy. These objective methods enabled us to compare the results of several reported studies in terms of racial variations [17,25]. For example, the b* value was changed by the addition of radiotherapy to yellowish in a statistically significant manner in Momm's study [4], but was not significant according to our data, partly because of pre-existing ethnic color variations ( Table 2).…”
Section: Discussionmentioning
confidence: 67%
“…In a recent dermatology study (funded by Proctor & Gamble), an in-depth color assessment of 407 females (note that males were not part of the study) showed that unexposed skin color was relatively constant across the entire country, whereas exposed skin color differed (Wei et al 2007). The sponsors of such a study, no doubt, are looking to uncover ways to target the female population for skin whitener products.…”
Section: Introducing Skin Tone Tension: Derived From the Consumer Motmentioning
confidence: 96%
“…Using these coordinates, we can determine the ITA (Individual Typological Angle) which is proportional to the degree of pigmentation of the skin. The darker the skin, the smaller the angle [45,46]. However, it is regrettable that the minimum number of subjects required by the Colipa in order to obtain valid results is only 10.…”
Section: Information Concerning the Volunteersmentioning
confidence: 99%